Trasplante de microbiota fecal en un paciente con parvovirosis canina: reporte de caso clínico - Pinilla León, Juan Carlos (2021)
It is reported the case of a four-month-old puppy that was admitted to the consultation at the veterinary clinic «Vet Center», Bucaramanga, Colombia, due to a severe gastroenteric disturbance. The patient showed signs of depression, vomiting, dehydration, and fever. The haematological evaluation revealed slight anaemia, and the canine parvovirus test was positive. For the stabilization and treatment of the patient, an intravenous catheter was placed for the infusion of intravenous lactated Ringer’s solutions, antibiotics, antiemetics, and vitamins. In addition, a faecal microbiota transplant was performed as additional therapy after 12 hours of hospitalization, repeating at 12 hours, giving satisfactory results that are discussed in this clinical report.